Application of Andragogy in Community Empowerment to Fulfill the Educational Needs of Children with Disabilities Through a Field School Approach - Fadly Halim Hutasuhut; Ahmad Ahmad; Hardika Hardika; Latief Bustami; Zulkarnain Nasution; Endang Redjeki; Supriyono Supriyono; Ranti Novianti (Universitas Negeri Padang, 2023)
The use of field schools is considered the best approach to accelerate the empowerment stages as well as the process of understanding knowledge and acquiring skills through joint activities in the community directly. This research aims to obtain information about the principles of andragogy in empowering the community to meet the educational needs of Children with Special Needs through the Field School Approach. This research is descriptive research with a qualitative approach. Data collection in this research was carried out through observation, interviews and documentation techniques. Data analysis techniques in this research include data reduction, data presentation and drawing conclusions. Triangulation is used to explain the validity of data by using source triangulation and technical triangulation. The results of this research obtained data that the principles of andragogy applied to Field School activities can create community empowerment. Key words : andragogy, community empowerment, ABK education, field schools